Variability in phytic acid and phytase levels and utilization of synthetic hexaploids for enhancing phytase levels in bread wheat - Vashishth, Amit; Ram, Sewa; Veniwal, Vikas (Journal of Cereal Research, 2017)
Phytic acid and phytase levels in wheat grains have greater influence on the bioavailability of micronutrients to human beings. Hence in the present investigation, two hundred fifty seven wheat genotypes including 168 synthetic hexaploids and 89 wheat cultivars were used to assess variability in phytase and phytic acid levels. The phytic acid content showed 1.5 fold variations from 1.03 to 1.58% with the mean value of 1.34% in bread wheat cultivars while higher variability (2.1 fold)was exhibited in synthetic hexaploids ranging from 0.93 to1.98% with the mean value of 1.35%. There were 4.1 fold differences in phytase levels in wheat cultivars varying from 284 to 1155 FTU/Kg with the mean value of 516 FTU/Kg and 7.9 fold in synthetic hexaploids varying from 255 to 2025 FTU/Kg with the mean value of 751 FTU/Kg. There was very strong correlation (R2=0.89)in phytase levels between duplicate samples of the wheat flours demonstrating high reproducibility of direct assay method used in this investigation. The method has additional advantage of analysing small quantityof materials available in the segregating generations of breeding programme.The selected synthetic hexaploids having high phytase levels are useful source for improving phytase levels in bread wheat cultivars.DOI:10.25174/2249-4065/2017/69945